A well site reclamation prioritisation model framework. Issue 3 (25th September 2015) - Thiessen, Ron J.; Achari, Gopal
Abstract : There are approximately 60 000 oil and gas well sites in Alberta that are abandoned but not reclaimed. This number is growing at approximately 10% per year. Currently, there is no regulatory requirement to reclaim well sites within a defined period after abandonment. The government regulator is reviewing this issue and is considering options to improve timely reclamation. In preparation for this change, the article provides the structure of a model to prioritise oil and gas well site reclamation across a portfolio of sites according to negative environmental, social and economic impacts. Adverse environmental receptor effects, adverse public response, environmental liability and property value diminution are used to quantify these impacts. Ordinal logistic regression and partial order methods to classify and rank well sites are applied in the model. A case study illustrates the prioritisation model.